Carthamus tinctorius L. protects cerebral ischemia/reperfusion injury via arachidonic acid/p53-mediated apoptosis axis - Chen, Junren; Wu, Liujun; Xie, Xiaofang; Peng, Cheng (Frontiers in Pharmacology, 2024)
IntroductionStroke is a debilitating disease and the second leading cause of death worldwide, of which ischemic stroke is the dominant type. Carthamus tinctorius L., also known as safflower, has been used to treat cerebrovascular diseases, especially ischemic stroke in many Asian countries. However, the underlying mechanisms of safflower in preventing ischemic stroke remains elusive. This study aims to elucidate the potential of safflower as a drug candidate for the prevention of ischemic stroke and to delineate its protective effects and potential mechanisms in a rat model of cerebral ischemia-reperfusion injury (CI/RI).MethodsThe aqueous extract of safflower (AESF) was verified using HPLC-UV, HPLC-MS, and TLC. The inhibitory effect of AESF on platelet aggregation was detected in vitro and in zebrafish and mice. A CI/RI model in rats was established by middle cerebral artery occlusion and reperfusion to study the protective effect of AESF on ischemic stroke. 2,3,5-triphenyltetrazolium chloride, hematoxylin and eosin, and Nissl’s staining were employed to evaluate the pathological changes of brain tissue. In addition, metabolomics, ELISA, and Western blot were used to uncover the molecular alteration induced by AESF.ResultsAESF significantly inhibited platelet aggregation in vitro, reduced the thrombogenesis in zebrafish, and prolonged clotting time in mice. In addition, AESF alleviated neurological dysfunction, cerebral oedema, cerebral infarct size, cerebral histopathological damage induced by ischemia-reperfusion, improved neuronal survival, increased serum levels of SOD and CAT, and decreased levels of iNOS and NO. Metabolomics revealed that AESF attenuated the metabolic disturbances in brain caused by I/R injury via regulating 38 metabolites particularly related to the arachidonic acid (AA) metabolism. Moreover, AESF elevated the serum levels of 6-keto-PGF1α, a pivotal metabolite of AA, downregulated the protein expression of p53, Bax, cleaved caspase-9, cleaved caspase-3, and cleaved caspase-8, and upregulated that of Bcl-2.ConclusionAESF mitigated CI/RI through preventing platelet aggregation, alleviating oxidative stress, and suppressing apoptosis partially via modulating AA metabolism/p53-mediated apoptosis axis.